Identifikasi Pengaruh Penerapan Model Cooperatif Learning terhadap Nilai-nilai Sosial Siswa pada Mata Pelajaran Sejarah di MAN 1 Pekanbaru - Norerlinda Norerlinda (Lembaga Anotero Scientific Pekanbaru, 2022)
This study aims to identify the effect of applying the cooperative learning model to students' social values ​​in history learning at MAN 1 Pekanbaru. In this study using descriptive qualitative analysis research method. The research subjects consisted of 32 class X students and history science teacher. The research data were obtained from the results of a questionnaire analysis of students and teachers in history learning class X. The results showed that the cooperative learning model was effective for increasing students' social values ​​compared to the ordinary (expository) learning model. In addition, the results of the study obtained findings on the learning process which indicated that it led to improving the quality of students' self.